2019
DOI: 10.1038/s41467-019-12745-x
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-mediated gene silencing reveals involvement of the archaeal S-layer in cell division and virus infection

Abstract: The S-layer is a proteinaceous surface lattice found in the cell envelope of bacteria and archaea. In most archaea, a glycosylated S-layer constitutes the sole cell wall and there is evidence that it contributes to cell shape maintenance and stress resilience. Here we use a gene-knockdown technology based on an endogenous CRISPR type III complex to gradually silence slaB, which encodes the S-layer membrane anchor in the hyperthermophilic archaeon Sulfolobus solfataricus. Silenced cells exhibit a reduced or pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 72 publications
(113 reference statements)
3
49
1
Order By: Relevance
“…Previous work has suggested that SSV1 adsorption requires the S‐layer in S. solfataricus P1 (Stedman et al, ; Zink et al, ). We have shown that S. islandicus lacking the outer S‐layer (SlaAB) is viable and contained pili and archaellum, although the archaellum are nonmotile in this strain (Zhang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has suggested that SSV1 adsorption requires the S‐layer in S. solfataricus P1 (Stedman et al, ; Zink et al, ). We have shown that S. islandicus lacking the outer S‐layer (SlaAB) is viable and contained pili and archaellum, although the archaellum are nonmotile in this strain (Zhang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Inner face net negatively charged due to an excess of carboxyl groups [7,8,24] Antifouling, non-sticky outer surface [7,11,28] Self-assembly capability in aqueous media, on the air/water interface, on lipid films, and on solid surfaces like metals (gold, silver, platinum, stainless steel), glass, silicon, silicon oxide and nitride, mica, polymers (e.g., polystyrene, polyester, cellulose, polydimethylsiloxane (PDMS), indium tin oxide (ITO), highly oriented pyrolytic graphite (HOPG), and carbon nanotubes [7,9,[28][29][30] S-layer proteins have so far suggested to mediate a broad range of specific biological functions, including protection against (e.g., bdellovibrios, bacteriophages, and phagocytosis) promoters for cell adhesion (e.g., to host enzymes and cells, immune-modulators, surface recognition, molecular sieve, molecule and ion traps, antifouling coatings, and virulence factors in pathogenic organisms) [7,23,31,32]. Moreover, the S-layer lattice is involved in the determination of cell shape and can aid in the cell division process in archaea possessing S-layers as the exclusive envelope component external to the cytoplasmic membrane [32][33][34][35].…”
Section: General Featuresmentioning
confidence: 99%
“…1) [29][30][31][32][33][34]. Recently, we used this technology to silence the gene encoding an essential translation initiation factor, aIF5A [32], and the S-layer anchor, SlaB [31] in S. solfataricus, enabling a phenotypic analysis of the depletion cultures. Silencing of slaB caused severe growth defects and perturbed cell division, limiting our ability to obtain stable lines with a silence efficiency of greater than 75% [31].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we used this technology to silence the gene encoding an essential translation initiation factor, aIF5A [32], and the S-layer anchor, SlaB [31] in S. solfataricus, enabling a phenotypic analysis of the depletion cultures. Silencing of slaB caused severe growth defects and perturbed cell division, limiting our ability to obtain stable lines with a silence efficiency of greater than 75% [31]. This indicated that, under the applied growth conditions, SlaB might execute an essential function in S. solfataricus, even though it was shown to be non-essential in S. islandicus [3].…”
Section: Introductionmentioning
confidence: 99%